Play dirty - Brown, Sandra (New York : Pocket Books, 2007)
A disgraced football quarterback, a Texas millionaire, an obsessed crooked detective they all play the game, but not everyone can play to win. From the master of romantic suspense and bestselling author of Ricochet comes a gripping story of playing for passion, redemption, and love'with deadly consequences. After five long years in federal prison, Griff Burkett is a free man. But the disgraced Cowboys quarterback can never return to the life he knew before he was caught cheating.
Keywords: Rich people -- Crimes against -- Fiction; Police -- Texas -- Dallas -- Fiction; Detective and mystery fiction